Gate-All-Around Cylindrical Nanowire FET-Based Room Temperature Ammonia Sensor for Diagnostic Applications - Ghosh, Sukanya; Rajan, Lintu (IEEE journal on flexible electronics, 2024)
Demonstrated through this research is an inspection of gate-all-around (GAA) cylindrical nanowire field-effect transistor (NWFET), concentrating on its ammonia (NH3) sensing performance for diagnostic purposes under room temperature (RT). Apart from effectively minimizing the short-channel effects (SCEs) owing to the improved gate strength, this multigated structure elevates current driving capability and is compatible with regular complementary metal-oxide-semiconductor (CMOS) processes. A systematized investigation of the sensing behavior has been illustrated through effectual modifications in molybdenum (Mo) and ruthenium (Ru) catalytic metal gate work functions depending on the concentration of NH3 arriving at the metallic surface. A concentration-reliant in-depth inspection has been elucidated with respect to the electric field and transfer characteristics. The sensing potentiality of the proposed NWFET has been assessed under the target NH3 environment with reference to the transformation in distinguished parameters for, e.g., ON-current ( I_{\text {ON}} ), OFF-current ( I_{\text {OFF}} ), transconductance (gm), subthreshold slope (SS), threshold voltage ( V_{\text {TH}} ), and so on., using the ATLAS simulator. The optimally constructed ammonia sensor demonstrates excellent I_{\text {ON}} / I_{\text {OFF}} ratios of approximately {\sim }{{10}}^{{8}} and {\sim }{{10}}^{{9}} significant I_{\text {OFF}} sensing responses of {\sim }{2.32} × {{10}}^{{2}} and {\sim }{1.28} × {{10}}^{{2}} , large \text {g}_{\text {m}} sensing outcomes of 99.90% and 99.67%, significant SS sensing outputs ( S_{\text {SS}} ) of ~83% and ~62.5%, better threshold voltage sensing responses ( S_{\text {VTH}} ) of ~52.3% and ~34.4%, respectively, for Mo and Ru metallic gates under 1.04-ppm NH3 concentration at RT. The operation of the proposed GAA NWFET in the subthreshold region at RT makes it a promising candidate in terms of low power consumption and cost-effectiveness.